Bimaxillary Protrusion - A Case Report - Halwa, Hemant Kumar; Yadav, Sumit Kumar; Dutta, Kishor; Gupta, Sandeep Kumar; Shrestha, Raju; Shah, Anish Kumar (Journal of Universal College of Medical Sciences, 2019)
Correction of a severe bimaxillary protrusion with maximum anchorage can be challenging. This case report describes the treatment of a girl with a bimaxillary protrusion. Orthodontic treatment included extraction of her 4 first premolars. The total treatment time was 18 months. Her dental proclination and facial appearance was significantly improved.